KEADILAN RESTORATIF BAGI KORBAN PENYALAHGUNAAN NARKOTIKA: OPTIMALISASI KAMPUNG TANGGUH KABUPATEN PATI DALAM PERSPEKTIF INTEGRATED CRIMINAL JUSTICE SYSTEM - Lailatul Nur hasanah (JOURNAL IURIS SCIENTIA, 2026)
The law enforcement of narcotics crimes in Indonesia is currently faced with a paradigmatic misalignment between punitive-retributive and restorative recovery approaches. This study aims to analyze the effectiveness and accountability of law enforcement officials in differentiating sanction articles between dealers and users, identify the determinant factors inhibiting the implementation of rehabilitation policies at the rural level, and formulate strategies to optimize the "Kampung Tangguh" (Anti-Narcotics Resilient Village) program in Pati Regency. Utilizing a normative juridical legal research method with a descriptive-qualitative specification, this study relies on secondary data sourced from primary legal materials, such as Law Number 35 of 2009 concerning Narcotics, and secondary legal materials from scientific legal literature. All legal materials were collected through library research and analyzed using deductive-inductive reasoning methods based on the principle of functional differentiation within the Integrated Criminal Justice System (ICJS). The results indicate that law enforcement in Pati Regency has not been effective and accountable due to inconsistencies and anomalies in article application (Article 114 versus Article 127) at the investigation stage, which tends to criminalize drug victims into correctional institutions, thereby triggering high rates of recidivism. The main inhibiting factors for rehabilitation include the psychological vulnerability of adolescents in free social circles, economic motives of lower-class workers (drivers and casual laborers) to maintain physical stamina, strong cultural social stigma within families, and the structural pathology of punitive law enforcement. As a solution, this study offers a novelty by deconstructing "Kampung Tangguh" from a ceremonial model into a Community-Based Restorative Justice Hub. This strategy is manifested through the institutionalization of a Village Restorative Forum as a formal case filter, a Family-Enforced Rehabilitation scheme with positive communal activity substitution (sports, herbal medicine, and religious activities), and digitalized monitoring via a Civic Reward System to actualize a fair principle of equality before the law.